EU Regulatory Models for Platforms on the Content and Carrier Layers: Convergence and Changing Policy Patterns - Andrej Savin (Nordic Journal of Commercial Law, 2018)
Digital “intermediaries” have been the subject of the lawmakers’ interest both in the EU and elsewhere for at least two decades now. In recent years, however, and coinciding with the introduction of the new Digital Single Market Strategy in 2015, “platforms” in specific - rather than “intermediaries”, “information society services (ISSs)” or “networks” - have incresingly been the target of EU regulators’ attention. This article traces the EU’s increased focus on platforms and argues that its source can be found in a desire to respond to technology convergence. The first part of the article looks at why convergence and the emerging platform regulation stand in a relationship and attempts to outline the boundaries of that relationship. The second part argues that the EU has already undergone a regulatory shift from “services” to “platforms” and traces this idea from its 2015 DSM Strategy origins to several other documents, including the 2016 Communication on Platforms. The third part looks at how the emergence of the idea and its elevation to a policy goal has already prompted changes in each of the three regulatory layers. The concluding part establishes that the EU policy shift from ISSs, networks and services as main regulatory units to platforms is sector-specific and prompted by attempts to address convergence. I argue that this approach may not necessarily be beneficial and look into alternatives involving a rethink of platform regulation across rather than within different layers.